Comparison of Two Methods of Estimating 48-month Tooth Loss Incidence - Gregg H. Gilbert, DDS, MBA; John S. Rose, MPH; Elmire D. Cantey, BS, RDH; Janet L. Earls, BS, RDH; (Blackwell Synergy, 2002)
This paper quantifies validity of self-reported tooth loss, compares incidence using two methods (semiannual self-report, biannual clinical examination), and compares conclusions about risk factors for tooth loss using these two methods